2014
DOI: 10.1002/hipo.22256
|View full text |Cite
|
Sign up to set email alerts
|

Memory‐related eye movements challenge behavioral measures of pattern completion and pattern separation

Abstract: The hippocampus creates distinct episodes from highly similar events through a process called pattern separation and can retrieve memories from partial or degraded cues through a process called pattern completion. These processes have been studied in humans using tasks where participants must distinguish studied items from perceptually similar lure items. False alarms to lures (incorrectly reporting a perceptually similar item as previously studied) are thought to reflect pattern completion, a retrieval-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
93
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 30 publications
(68 reference statements)
13
93
1
Order By: Relevance
“…The problem, in other words, may have been one of memory consolidation (Wixted, 2004). Such a conclusion is fully in line with the recent observation by Molitor et al (2014), using an eye-tracking measure to assess false alarms in a continuous recognition task like that used here: apparently errors in the task of reporting 'old' to similar items were associated with decreased fixations during the earlier presentations of those items. In a temporally densely packed sequence of items, the problem presumably was one of insufficient encoding of images into memory.…”
Section: Implications For Behavioural Measures Of Pattern Separationsupporting
confidence: 89%
See 1 more Smart Citation
“…The problem, in other words, may have been one of memory consolidation (Wixted, 2004). Such a conclusion is fully in line with the recent observation by Molitor et al (2014), using an eye-tracking measure to assess false alarms in a continuous recognition task like that used here: apparently errors in the task of reporting 'old' to similar items were associated with decreased fixations during the earlier presentations of those items. In a temporally densely packed sequence of items, the problem presumably was one of insufficient encoding of images into memory.…”
Section: Implications For Behavioural Measures Of Pattern Separationsupporting
confidence: 89%
“…Yet Yeung et al found that mean eye fixations in their older adults did not differ across old repeated items and items sharing high similarity; apparently new items TIME MANAGES INTERFERENCE 6 were falsely viewed as old. This may have reflected either impoverished encoding in the study phase (Molitor, Ko, Hussey & Ally, 2014) or failure to identify novel visual features.…”
Section: Time Manages Interference 3 Time Manages Interference In Vismentioning
confidence: 99%
“…The current lesion data might also inform the debate on process interplay, and may be applied to the question of whether pattern separation and pattern completion are two sides of the same coin or opposite ends of a continuum (Hunsaker & Kesner, 2013;Molitor, Ko, Hussey, & Ally, 2014;Vieweg et al, 2015;Yassa et al, 2011). A key element of this debate -as with other topics in cognitive neuroscience -concerns the process purity of the behavioral paradigms used to assess these cognitive operations (e.g., Molitor et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…A key element of this debate -as with other topics in cognitive neuroscience -concerns the process purity of the behavioral paradigms used to assess these cognitive operations (e.g., Molitor et al, 2014). In the current study, even though it is assumed that the MST and MIC approximate pattern separation and pattern completion, respectively, there are other neural computations, both upstream and downstream from the dentate gyrus, which can help differentiate new information from preexisting memory traces (Deuker et al, 2014;Leutgeb et al, 2007;Myers, & Scharfman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Simply put: increased behavioral pattern separation should shift only the lure distribution. As mentioned above regarding dualprocess theories of memory recognition, a broader consideration when using these paradigms, however, is that there may be multiple processes contributing to the behavior (Molitor et al 2014). Therefore, behavioral paradigms alone cannot usually suffice for conclusions about neural processes (Santoro 2013), but a better behavioral measure can help to test whether there is indeed a relationship.…”
mentioning
confidence: 99%